Pelatihan Pembuatan Pupuk Kompos Ampas Tebu - Urai Suci Y.V. Indrawati; M, Leony Agustine; Hazriani, Rini (Jurnal Pengabdian kepada Masyarakat Nusantara, 2023)
There are many kinds of organic fertilizer, such as: compost, green manure, guano, and so on. Providing organic fertilizer can increase soil fertility, increase the nutrient content in the soil and help form green infrastructure in the surrounding environment (Hapsari and Chalimah, 2013). One of the ingredients for making organic fertilizer is sugar cane bagasse. This community service aims to provide training and make sugarcane bagasse compost fertilizer to be applied to crop cultivation. In making sugarcane bagasse compost fertilizer, Effective Microorganism 4 (EM4) is needed as an activator. The training and making bagasse compost fertilizer went smoothly and the making of bagasse compost fertilizer was successful and could be applied immediately after an evaluation was carried out after 1 month.